2006
DOI: 10.1182/blood.v108.11.142.142
|View full text |Cite
|
Sign up to set email alerts
|

pak2a Mutations Cause Cerebral Hemorrhage in Redhead Zebrafish.

Abstract: Zebrafish are a powerful vertebrate model system for the study of human disease as they share many molecular pathways with mammals. Of note, nearly all of the mammalian coagulation factors are also highly conserved in fish. As part of a whole genome ENU mutagenesis screen, we identified a mutant zebrafish which displayed intraventricular hemorrhage between 2–3 days post fertilization (dpf), which we named redhead. Using an F2 intercross strategy, we mapped this recessive mutant to a 100 kilobase interval on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…26,30 Multiple vascular mutants have been described in zebrafish with intracranial hemorrhage as a primary phenotype secondary to various mechanisms, including defects in vascular development, patterning, integrity, and remodeling. [27][28][29] Our analysis did not reveal any such vascular phenotypes, suggesting that the consequences of F10 loss are solely defects in hemostasis. This implies that thrombin generation is not a key player in zebrafish vasculogenesis or operates through non-F10-dependent pathways.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…26,30 Multiple vascular mutants have been described in zebrafish with intracranial hemorrhage as a primary phenotype secondary to various mechanisms, including defects in vascular development, patterning, integrity, and remodeling. [27][28][29] Our analysis did not reveal any such vascular phenotypes, suggesting that the consequences of F10 loss are solely defects in hemostasis. This implies that thrombin generation is not a key player in zebrafish vasculogenesis or operates through non-F10-dependent pathways.…”
Section: Discussionmentioning
confidence: 60%
“…15 Thus, we have turned to the zebrafish model (Danio rerio) with advantages that include high fecundity, external and transparent development, ease of manipulation and maintenance, accessibility of genetic techniques and imaging, as well as extensive conservation of the hemostatic and vascular systems as we and others have demonstrated. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In this article, we report targeted mutagenesis of zebrafish f10 through genome editing with transcription activator-like effector nucleases (TALENs). We find that loss of F10 results in late-onset lethality by 4 months of age secondary to intracranial and intra-abdominal hemorrhage, without any evidence of a vascular defect.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, we have identified an endothelial enhancer for the purpose of generating a useful reagent to drive gene expression in blood vessels. Accordingly, these Gateway compatible fli1ep constructs have been used to rapidly generate constructs for endothelial autonomous rescue experiments in the zebrafish redhead mutant (Buchner et al,2007). We have also constructed Gateway compatible Tol2 vectors containing the fli1ep fragment for generating N‐terminal fusions with 6xmyc, Egfp, and mCherry (data not shown and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This cassette was transferred to pTol2000 (kindly provided by Koichi Kawakami) that had been digested with Xho I and treated with Klenow. A description of the construction of the fli1ep containing vectors can be found elsewhere (Buchner et al,2007). In all cases, plasmids containing Destination cassettes were grown in ccdB ‐tolerant bacterial strains (Invitrogen) and maintained in the presence of both ampicillin and chloramphenicol.…”
Section: Methodsmentioning
confidence: 99%
“…(21) Positional cloning showed that the redhead mutation is located in the Pak2a gene, which is a downstream signaling partner of bPix. (22) In addition to BIRC2, the role of another IAP, survivin, was recently studied by knockdown of its expression in zebrafish. Downregulation of survivin expression resulted in perturbation of angiogenesis in vessels of the trunk, the eyes and the intestines, at least in part by an increase in endothelial apoptosis.…”
mentioning
confidence: 99%